The effectiveness of applying total quality management in Public Senior High School Kasihan 1 Bantul, Yogyakarta Indonesia - Suleiman Aden Jamaa (JOURNAL OF EDUCATION, 2010)
The objective-approach evaluation aimed to audit the school effectiveness on the five TQM components of services to students, physical environment and resources, human resource, processes and product(s). The study involved a quantitative method using a standard audit checklist (Sallis, 1998:138). A few modifications were made by dropping few items and grouping the indicators into the five total quality components. The checklist was used in two ways, first, through subjective approach involving the head teacher and 45 sample teachers. Second, by the researchers own objective quantitative observation. The result of the descriptive analysis shows differences in perception rating. The mean average of 3.0+ obtained for the five components items reveals an average perception. The conclusion here is that the five components mean average per component items is within the average effectiveness with slight variation